Mission Bambini and the “Children's Heart Program”: The Challenge of Congenital Heart Disease Among Emergency and Education - Marianeschi, Stefano M.; Albano, Giulia; Viola, Nicola; Barenghi, Alberto; Gusella, Alex (Frontiers in Pediatrics, 2022)
Introduction: Congenital heart disease is defined as abnormality in the cardiovascular structure or function that is present at birth and it is the most common cause of congenital anomalies.Approximately 90% of more than 1,000,000 children born per year with congenital heart disease worldwide receive suboptimal care or have no access to care at all. Furthermore, the mortality is likely underreported in Low-and Middle-Income Countries. Material and Methods: Mission Bambini Foundation is an Italian NGO founded in 2000, aiming at “helping and supporting children who are poor, sick, without education or physically and morally abused” in Italy and worldwide. In 20 years, through 1.700 projects, 1,4 million children have been supported in 75 Countries. In 2005, Mission Bambini launched the “Children’s Heart Program”. Discussion: Children’s Heart Program is based on long-term partnerships and on medical/surgical volunteering, in order to provide multidisciplinary education and training and technical support. Conclusion: in 15 years of humanitarian mission the education and training play a key role in order to raise the quality of pediatric cardiac service in low and middle incam countries